Prevalence and Severity of Dysphonia in Patients with Cystic Fibrosis: A Pilot Study. (July 2015) - Willis, John; Michael, Deirdre D.; Boyer, Holly; Misono, Stephanie
Objective: To assess the prevalence and severity of dysphonia in patients with cystic fibrosis sinusitis. We hypothesized that patients with CF sinusitis, compared with 2 control groups, would have higher self-reported prevalence of dysphonia and greater severity of dysphonia, according to patient-reported outcome measures as well as auditory-perceptual evaluation by expert listeners. Study Design: Cross-sectional comparative pilot study. Setting: Academic tertiary care clinic. Study Participants and Methods: Analysis included 37 study participants: 17 patients with CF sinusitis, 10 healthy individuals, and 10 patients with non-CF sinusitis. All participants completed the 10-item Voice Handicap Index (VHI-10) questionnaire and provided voice samples. On all samples, 6 blinded speech-language pathologists independently performed auditory-perceptual evaluation, using Consensus Auditory-Perceptual Evaluation of Voice. To assess severity of sinonasal symptoms, we used the 20-item Sinonasal Outcome Test (SNOT-20). Standard parametric and nonparametric statistical analysis was performed. Results: The differences between the 3 groups in prevalence of abnormal VHI-10 scores were not statistically significant. SNOT-20 scores were similar in the 2 sinusitis patient groups. VHI-10 scores were highest in patients with CF sinusitis, intermediate in patients with non-CF sinusitis, and lowest in healthy individuals ( P = .005). Auditory-perceptual evaluation demonstrated greater overall severity of dysphonia in patients with CF sinusitis compared with the 2 control groups ( P = .0005). Conclusions: Cystic fibrosis sinusitis appeared to be associated with worse vocal function as measured by patient self-report as well as auditory-perceptual evaluation of voice compared with patients with non-CF sinusitis and healthy controls. Further investigation in this area is warranted.